Depression Among Resident Doctors: Prevalence and Associated Factors in A Tertiary Institution in South-South Nigeria - Geraldine, Ndukwu U.; Temitope, Olamuyiwa E.; John, Affiong N. D. (International Journal of Innovative Research in Medical Science, 2022)
Background: Depression is an important contributor to the global burden of disease and it is associated with stress. It has been noted that being a doctor is stressful and residency training further increases the stress. Objective: This study determined the prevalence and factors associated with depression among resident doctors in a training tertiary health institution in South-South Nigeria. Methods: The study was a descriptive cross-sectional study in which 220 randomly selected resident doctors completed 4-point Likert scale self-administered Beck Depression Inventory-II (BDI-II) and a socio-demographic questionnaire. The BDI is a 21-item, rated on 4-point scale ranging from 0 to 3 totalling 63. The data was analyzed using Statistical Package for Social Sciences (SPSS) version 23. Bivariate analysis was performed using Pearson’s Chi square. A p value of < 0.05 was considered statistically significant. Results: In this study, 129 (58.6%) were males and 91 (41.4%) females. Majority were between the ages of 31-35 years 95(43.2%). Overall prevalence of depression was 16.8% (mild mood disturbances 9.1%, Borderline clinical depression 2.7% moderate depression 4.1% and extreme depression 0.9%). Sex, marital status and religion were associated with depression which were statistically significant. The proportion of resident doctors with depression was high among male resident doctors, age group 31-35 years, those married, Christian, Junior residents, those in training between 1-5 years and see lesser number of patients weekly. Conclusion: This study has demonstrated that about one-fifth of the resident doctors were depressed. Depression was significantly associated with sex, marital status, and religion.